The Rolling Stones get a new guitarist; Mick Taylor replaces Brian Jones (Module II, 2013)
England. London, Hyde Park. Footage of: Press in Hyde Park; Jagger's arrival; Mick Taylor posing and being interviewed; The Stones posing with Taylor; The Stones departure.